2020
DOI: 10.3390/cancers12040904
|View full text |Cite
|
Sign up to set email alerts
|

The Receptor Tyrosine Kinase RON and Its Isoforms as Therapeutic Targets in Ewing Sarcoma

Abstract: The receptor tyrosine kinase (RTK) RON is linked to an aggressive metastatic phenotype of carcinomas. While gaining interest as a therapeutic target, RON remains unstudied in sarcomas. In Ewing sarcoma, we identified RON among RTKs conferring resistance to insulin-like growth factor-1 receptor (IGF1R) targeting. Therefore, we explored RON in pediatric sarcoma cell lines and an embryonic Tg(kdrl:mCherry) zebrafish model, using an shRNA-based approach. To examine RON-IGF1R crosstalk, we employed the clinical-gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 52 publications
(118 reference statements)
0
1
0
Order By: Relevance
“…The early-stage animals are optically transparent, making it possible to track metastatic cell dissemination with high resolution in a large number of test subjects. This method has been used to investigate a novel mechanism of NOTCH-induced tumor suppression involving modulation of the deacetylase SIRT1 [ 386 ]; to test the effects of the MDM2 inhibitor Nutlin-3 in combination with the small molecule YK-4-279 [ 387 ]; a role for receptor tyrosine kinase RON in EwS metastatic progression [ 388 ]; and to demonstrate synergistic effects of aurora kinase A inhibitors when combined with FAK inhibitors [ 389 ]. In one particularly notable study, Franzetti and co-workers demonstrated that plasticity in the expression level and activity of the EWSR1-FLI1 oncofusion affects the balance of proliferative states with those favoring migration, invasion and metastasis [ 285 ].…”
Section: Scientific Perspectives On Clinical Enigmas Of Disseminated Ews Diseasementioning
confidence: 99%
“…The early-stage animals are optically transparent, making it possible to track metastatic cell dissemination with high resolution in a large number of test subjects. This method has been used to investigate a novel mechanism of NOTCH-induced tumor suppression involving modulation of the deacetylase SIRT1 [ 386 ]; to test the effects of the MDM2 inhibitor Nutlin-3 in combination with the small molecule YK-4-279 [ 387 ]; a role for receptor tyrosine kinase RON in EwS metastatic progression [ 388 ]; and to demonstrate synergistic effects of aurora kinase A inhibitors when combined with FAK inhibitors [ 389 ]. In one particularly notable study, Franzetti and co-workers demonstrated that plasticity in the expression level and activity of the EWSR1-FLI1 oncofusion affects the balance of proliferative states with those favoring migration, invasion and metastasis [ 285 ].…”
Section: Scientific Perspectives On Clinical Enigmas Of Disseminated Ews Diseasementioning
confidence: 99%